Spawning of the Indian major carps in battery of earthen pools - Bandyopadhyay, M K (Indian Journal of Fisheries, 2011)
Further, investigations were initiated on induced spawning of Indian major carps Catla catla, Labeo rohita and Cirrhinus mrigala) enclosed in a battery of earthen pools consisting of two longitudinally built compartments. A single source of continuous water flow was maintained in the earthen pools till the starting of spawning. The experimental system was designed and operated in a fish farm at Komakantia village, Puri District, Orissa. An attempt was made to induce spawning of the major carps (Catla catla, Labeo rohita and Cirrhinus mrigala). The experiment was conducted twice during July in 1989 and 1990 with a continuous inflow of water to the pools till the starting of spawning. The spawning was totally successful in the injected and non-injected females of C. mrigala while it was partial in the case of C. catla and L. rohita